2023
DOI: 10.1063/5.0161658
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen/phosphorus co-doped carbon decorated with metallic zinc for high-performance potassium-ion batteries

Abstract: Carbonaceous anodes of potassium-ion batteries (PIBs) hold sluggish adsorption and diffusion kinetics due to the large radius of K+, leading to poor cyclic stability and low specific capacity. Herein, an amorphous carbon material composed of N/P-doped active sites and trace amount of metallic zinc (Zn-NPC) is prepared through a facile self-sacrificing template method. Both experimental data and theoretical calculations indicate the co-doping of metallic zinc, and N/P atoms contribute to the low charge transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In the O 1s spectrum (Figure S2b), the 535.8 and 532.5 eV peaks were assigned to C−O and C�O bonds, respectively. 35,36 The results exactly revealed the existence of NHCs. The BET measurement was conducted (Figure S3), which showed that specific surface area values substantially increased during the synthesis process of NHCs.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…In the O 1s spectrum (Figure S2b), the 535.8 and 532.5 eV peaks were assigned to C−O and C�O bonds, respectively. 35,36 The results exactly revealed the existence of NHCs. The BET measurement was conducted (Figure S3), which showed that specific surface area values substantially increased during the synthesis process of NHCs.…”
Section: Resultsmentioning
confidence: 54%
“…To verify the elemental composition of NHCs, XPS was performed (Figures c and S2). The N 1s peaks 398.5, 400.6, and 401.5 eV were assigned to the pyridine-N, pyrrolic-N, and graphitic-N, respectively. In the C 1s spectrum (Figure S2a), the peaks indicated the existence of C–C, CO, and C–N bonds. In the O 1s spectrum (Figure S2b), the 535.8 and 532.5 eV peaks were assigned to C–O and CO bonds, respectively. , The results exactly revealed the existence of NHCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Moreover, their catalytic activity can be further improved by doping with heteroatoms (N, P, S, B and F) and morphology adjustment. 43 The former can increase the intrinsic activity by introducing more active sites. The latter can enhance the external performance by enlarging the reaction area.…”
Section: Bifunctional Catalystmentioning
confidence: 99%
“…Potassium-ion batteries (PIBs) have been considered for the application in the next generation of large-scale energy storage systems owing to their similar operating mechanism to lithium-ion batteries as well as the low cost and abundant resources of K. However, the large radius of K + (K + : 1.38 Å vs Li + : 0.76 Å) often leads to slow diffusion kinetics and collapse of the electrode structure during the potassiation/depotassiation processes, which is impeding the development of PIBs for practical applications. Therefore, exploring structurally stable electrode materials with fast kinetics is important to accelerating the commercialization of high-performance PIBs.…”
Section: Introductionmentioning
confidence: 99%